Novel Light Field Encoding Framework Based on Optical Flow and Phase Correlation - Storch, Iago; Corrêa, Douglas; Rosler, Igor; Palomino, Daniel; Bampi, Sergio; Zatt, Bruno (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2022)
This work proposes a novel Light Field encoding framework based on optical flow and phase correlation. This encoder works by com bining one reference sub-aperture image (SAI) with optical flow and phase correlation information of a few SAIs to synthesize all SAIs of the Light Field. In order to improve the quality of the synthesized Light Field, an HEVC encoder is modified to encode synthesis error and add a quality enhancement layer. The proposed encoder out performs JPEG Pleno 4D Transform Mode encoder and the HEVC anchor in lower bitrates. Also, it can be easily adapted to the existing multimedia infrastructure.